Efektivitas Analisis Beban Kerja Berbasis Elektronik (E-ABK) di Dinas Perumahan Rakyat dan Kawasan Pemukiman serta Pertanahan Kota Surabaya - Zikra, Rabbiul; Anysakurillah, Rosyidatuzahro (VISA: Journal of Vision and Ideas, 2024)
In the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis, workload analysis is defined as a process of collecting, recording, processing and compiling job data into job information. According to Hasibuan, "the steps for job analysis are as follows: Determining the use of the results of job analysis information, drawing up information about the background, selecting the muwakal (person to be assigned) to the position to be analyzed. According to Miles and Huberman, the data analysis technique used by researchers is data reduction, data presentation and conclusion drawing, as well as data validity techniques in this research using triangulation. This research will use Kreitner and Kinicki's effectiveness theory, namely goal achievement, resource acquisition, internal processes, and strategic constitutional satisfaction.1. Achievement of objectives implemented by the DPRKPP is in line with expectations by changing job descriptions and adjusting targets, frequency and working hours. 2. Acquisition of resources which is an indicator of this theory is very effective because with the E-ABK application, employee recruitment can be calculated using the Full formula. Time Equivalent, ABK Value will be a reference for regional officials in proposing additional employees for work effectiveness and efficiency. 3. Internal Process, carried out at DPRKPP with harmonious relationships between parties as a group and individually. The nature of openness carried out by the department also makes it easier for students to carry out monitoring and evaluation. 4. Satisfaction of strategic constituents. With the existence of regulations that are hierarchically tiered from Permenpan-RB to Perwali Surabaya, this has shown the readiness of various parties in implementing E-ABK.